Virus-Like Particle, Liposome, and Polymeric Particle-Based Vaccines against HIV-1 - Gao, Yong; Wijewardhana, Chanuka; Mann, Jamie F. S. (Frontiers in Immunology, 2018)
It is acknowledged that vaccines remain the best hope for eliminating the HIV-1 epidemic. However, the failure to produce effective vaccine immunogens and the inability of conventional delivery strategies to elicit the desired immune responses remains a central theme and has ultimately led to a significant roadblock in HIV vaccine development. Consequently, significant efforts have been applied to generate novel vaccine antigens and delivery agents, which mimic viral structures for optimal immune induction. Here we review the latest developments that have occurred in the nanoparticle vaccine field, with special emphasis on strategies that are being utilized to attain highly immunogenic, systemic and mucosal anti-HIV humoral and cellular immune responses. This includes the design of novel immunogens, the central role of antigen-presenting cells, delivery routes and biodistribution of nanoparticles to lymph nodes. In particular, we will focus on virus-like-particle (VLP) formulations and their preclinical uses within the HIV prophylactic vaccine setting.